Primeiro autovalor não nulo de uma hipersuperfície mínima na esfera unitária - Silva, Henrique Blanco da (2013)
The aim of this work is we study the first nonzero eigenvalue of the Laplacian operator compact hypersurfaces with constant mean curvature immersed in the unit sphere contained in Euclidean space. We will show that for the minimal case, we will have one of three possible estimates for the first eigenvalue and, as a consequence of a possible eigenvalue, this hypersurface will be isometric to sphere.